classification of radon hazard in urban planning focused to risk management - Castelluccio, Mauro; Giannella, Gianluigi; Lucchetti, Carlo; Moroni, Massimo; Tuccimei, Paola (Italian journal of engineering geology and environment, 2012)
This work deals with the evaluation of radon hazard in urban planning. According to the experiences developed in Europe and in the United States, we propose to associate the measurement of soil radon concentration at the minimum depth of 80 cm with the determination of soil gas permeability in order to calculate RP and RI radon indices. The values of these indices allow classifying the radon hazard of a future building site and planning technical actions to reduce and control indoor radon levels. The application of this procedure to two test-sites (Valle della Caffarella and Parco della Resistenza) located in central Italy and characterised by different geological setting and bedrock, demonstrate that the introduction of the intrinsic permeability helps to better describe the hazard level, reducing the seasonal variability that affects measurements. With a precautionary spirit, we suggest that a correction coef cient should be employed to summer measurements in order to minimise the underestimation of soil radon and radon indices that is commonly observed in dry and warm periods. July and August RP indices should be multiplied by 2, whereas June and September values times 1.5. No corrections are needed for winter determinations when highest values are reached.